2011
DOI: 10.2165/11590450-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Lower IQ is Associated with Decreased Clinical Response to Atomoxetine in Children and Adolescents with Attention-Deficit Hyperactivity Disorder

Abstract: Objectives: Atomoxetine is commonly used to treat attention-deficit hyperactivity disorder (ADHD) in children with a broad range of cognitive abilities. We examined the association between level of cognitive functioning as determined by IQ and clinical response during treatment with atomoxetine. Methods: The records of all the children and adolescents treated with atomoxetine at a university clinic in Catania, Italy, over a 3-year period were examined. A total of 55 clinically referred children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…However, this somewhat muted response rate is consistent with what has been reported with psychostimulants in children with ASD (RUPP, 2005) and in children with intellectual disability (Aman, Buican, & Arnold, 2003). Indeed as in Mazzone et al's (2011) study of ATX, Aman et al (2003) found that lower IQ was associated with a poorer response rate to methylphenidate in children with ID and ADHD. It suggests that response rates to noradrenergic and dopaminergic ADHD medicines may be diminished in young people with IDD relative to responses of TD children with ADHD.…”
Section: Discussion: State Of the Research In The Developmental DImentioning
confidence: 89%
“…However, this somewhat muted response rate is consistent with what has been reported with psychostimulants in children with ASD (RUPP, 2005) and in children with intellectual disability (Aman, Buican, & Arnold, 2003). Indeed as in Mazzone et al's (2011) study of ATX, Aman et al (2003) found that lower IQ was associated with a poorer response rate to methylphenidate in children with ID and ADHD. It suggests that response rates to noradrenergic and dopaminergic ADHD medicines may be diminished in young people with IDD relative to responses of TD children with ADHD.…”
Section: Discussion: State Of the Research In The Developmental DImentioning
confidence: 89%
“…Other factors – such as symptom control, parent/caregiver’s decision to discontinue, dislike of medication, and dosing inconvenience – were reported less frequently. Discontinuation reasons for children and adolescents treated with nonstimulants were detailed in only four studies 6669. All four of these studies cited treatment ineffectiveness/suboptimal response, three cited adverse effects, and one cited poor adherence to treatment as reasons for discontinuation.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding three studies that did not report any data concerning AEs,17 27 31 one interim analysis29 and one study presented as an abstract in a congress,24 11 studies were evaluated 16 18–23 25 26 28 30…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were retrospective chart reviews,16 21 25 two analysed data collected prospectively in an Italian register18 28 and six were prospective trials 19 20 22 23 26 30…”
Section: Resultsmentioning
confidence: 99%